2003
DOI: 10.3758/bf03196494
|View full text |Cite
|
Sign up to set email alerts
|

Timed picture naming in seven languages

Abstract: Timed picture naming was compared in seven languages that vary along dimensions known to affect lexical access. Analyses over items focused on factors that determine cross-languageuniversals and cross-languagedisparities. With regard to universals, number of alternative names had large effects on reaction time within and across languages after target-name agreement was controlled, suggesting inhibitory effects from lexical competitors. For all the languages, word frequency and goodness of depiction had large e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
417
7
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(471 citation statements)
references
References 56 publications
21
417
7
9
Order By: Relevance
“…From this, it follows that the more visually complex an icon is (and therefore the more features it has), the more time will be involved in binding features together, producing slower response times for more complex signs. However, Forsythe et al (2008) have shown that there is a correlation between icon familiarity and visual complexity and that this is the result of familiar icons being perceived as simpler (see also Bates et al, 2003;Chi & Dewi, 2014). This suggests that searching for icons in arrays may have a topdown, as well as a bottom-up, processing component and aligns with later theoretical approaches to search which have emphasised the importance of prior knowledge of shapes, objects, or complex scenes (Bundesen, 1998;Green & Oliva, 2009;Joubert et al, 2007;Logan, 1996;Malcolm & Henderson, 2009;Rousselet et al, 2004;.…”
Section: Processing Fluency and Appeal Evaluationsmentioning
confidence: 80%
See 1 more Smart Citation
“…From this, it follows that the more visually complex an icon is (and therefore the more features it has), the more time will be involved in binding features together, producing slower response times for more complex signs. However, Forsythe et al (2008) have shown that there is a correlation between icon familiarity and visual complexity and that this is the result of familiar icons being perceived as simpler (see also Bates et al, 2003;Chi & Dewi, 2014). This suggests that searching for icons in arrays may have a topdown, as well as a bottom-up, processing component and aligns with later theoretical approaches to search which have emphasised the importance of prior knowledge of shapes, objects, or complex scenes (Bundesen, 1998;Green & Oliva, 2009;Joubert et al, 2007;Logan, 1996;Malcolm & Henderson, 2009;Rousselet et al, 2004;.…”
Section: Processing Fluency and Appeal Evaluationsmentioning
confidence: 80%
“…For example, our familiarity with the abstract icon representing 'female' in Figure 2d allows us to identify it more quickly and effectively compared with the pictorial rabbit icon representing 'fast processing' (Figure 2b). In the picture naming literature, rated familiarity of the pictures is also a strong and consistent predictor of naming times and is thought to reflect the ease with which semantic representations can be accessed from long-term memory (Alario et al, 2004;Bates et al, 2003;Ellis & Morrison, 1998;Lambon-Ralph et al, 1998;Snodgrass & Yuditsky, 1996). Thus, when icons are presented, ease of processing is likely to be determined by the extent to which interface users are able to access an appropriate function, or meaning, reflecting our familiarity with the icon-function relationship.…”
Section: Familiaritymentioning
confidence: 99%
“…Overall, there were 54 masculine and 56 feminine picture targets. All targets were imageable nouns compiled from various published studies and databases-e.g., LaChapelle (1984a, 1984b), Dunn and Dunn (1981) and Snodgrass and Vanderwart (1980); see Bates et al (2000Bates et al ( , 2003representing mostly inanimate objects, as well as 22 pictures of animals with same grammatical gender across sexes (e.g., pingüino-penguin; except for dog = perro/perra and bear = oso/osa; both more frequent in masculine form in Spanish) and 1 gender-ambiguous picture of a clown face. Six items were plural (socks, eggs, peanuts, scissors, flies, and eyes).…”
Section: Methodsmentioning
confidence: 99%
“…Each participant took language tests that have been culturally adapted for native Cantonese speakers in Hong Kong, including (a) Spoken Word-Picture Matching test (Law, 2004), (b) Written Word-Picture Matching test (Law, 2004), (c) an adopted Cantonese version of the Pyramid and Palm Tree Test (adapted PPTT; Law, 2004), and (d) Synonym Judgment Test (SJT; Law, 2004) for assessing verbal semantic abilities; (e) selected items from the PPTT (Howard & Patterson, 1992) and Associative Match test in the Birmingham Object Recognition Battery (Riddoch & Humphreys, 1993) for assessing nonverbal semantic abilities; (f ) selected items from oral pictured object naming (Snodgrass & Vanderwart, 1980); and (g) oral pictured action naming (Bates et al, 2003) for assessing oral naming abilities. In addition, each PWA was evaluated by the Cantonese version of the Western Aphasia Battery (CAB; Yiu, 1992) for classification of aphasia subtypes and assessment of aphasia severity in terms of AQ, and the Action Research Arm Test (Lyle, 1981) to evaluate the changes in limb functions resulting from hemiplegia.…”
Section: Databasementioning
confidence: 99%